EFFECT OF DESIGN THINKING TO DEVELOP MARINE AND COASTAL ENVIRONMENTAL ATTITUDES - ABDUL TALIB, CORRIENNA; FARUKU ALIYU, FARUKU ALIYU; ABDUL MALIK, ADI MAIMUN; KANG HOOI SIANG, KANG HOOI SIANG; CHIN CHEE KEONG, CHIN CHEE KEONG; ISMAIL, MOHD ERFY; SAMSUDIN, MOHD ALI (UMT, 2023)
: This paper analysed the effect of the design thinking approach on the student’s awareness of marine and coastal environmental sustainability. The paper employed an experimental design and utilised a sample of thirty-five students using an online questionnaire through a google form validated by experts in educational research. Based on the analysis of their responses, the findings revealed that the respondents are fully aware of the harmful effects of marine and coastal pollution on human lives. It is imperative to prevent the proliferation of plastic products in the environment, even if it means sacrificing something to slow down marine and coastal pollution. Also, students agreed that there is a need for awareness that despite the continual contamination of rivers and oceans, nature’s purifying processes soon return to normal when they have good management. The paper concluded that even with the awareness of marine and coastal pollution, there is still a lack of understanding of the holistic consequences of marine plastic and the resulting impact on ecosystem services, as well as the implications for human health, society, and the economy. It is limited to a small sample size, quantitative data and simple statistical tools of frequency and percentages and recommended that an approach such as design thinking focusing on marine and coastal pollution could be used in schools and the government needs to introduce harsh measures to halt marine and coastal pollution since very few people will regulate themselves.